Pengoptimalan Perawatan Deepwell Cargo Pumps untuk Memperlancar Kegiatan Bongkar di MT. Prima Lautan 1 - Anita Rahayu; Fitri Suprapti; Kirtyana Nindita; Widar Bayu Wantoro (Jurnal Maritim Polimarin, 2026)
This study aims to identify factors causing decreased performance of the deepwell cargo pump and the maintenance measures taken to prevent delays in the unloading process on the MT Prima Lautan 1. The research method used was qualitative descriptive, with data collected through observation, interviews, and literature review during practical activities at sea. The results showed that the main factors causing delays in the unloading process on the MT Prima Lautan 1 were inadequate performance of the deepwell cargo pump, and suboptimal maintenance. In addition to technical aspects, it was found that the crew's lack of understanding of maintenance procedures also exacerbated the damage. To address this problem, a series of steps can be taken, such as maintenance and lubricating the deepwell cargo pump, which can improve its performance. Consistent implementation of a planned maintenance system in accordance with the manual and company's SMS can improve the efficiency and safety of ship operations. Therefore, this study emphasizes the importance of preventive maintenance and ongoing training for ship crews to reduce the risk of damage and operational delays.